Analisis Komponen Koleksi Berdasarkan Instrumen Akreditasi Perpustakaan Institut Bisnis dan Informatika Islam - Yoanda, Sely (UIN Raden Intan Lampung, 2021)
This study aims to determine the extent to which the Indonesian Institute of Business and Informatics Library prepares for library accreditation, especially in the collection component. The instrument used in this study is the university library accreditation instrument listed in the national library regulations of the Republic of Indonesia number 10 of 2018. The library collection component has 26 key indicators with a maximum weight of 20. This research method uses a descriptive quantitative approach. The technique of collecting data is through observation and structured interviews with the drafting team for the accreditation of the Indonesian Institute of Business and Informatics Library. The results showed that the Indonesian Institute of Business and Informatics Library based on the university library accreditation instrument was estimated to get a value of 13.7 out of a maximum weight of 20 for the collection component. This means that the preparation of the Indonesian Institute of Business and Informatics Library is still not optimal and must be improved again. The library of the Indonesian Institute of Business and Informatics has the potential to increase its accreditation value derived from 16 other indicators which include the availability of collection development policies, implementation of policies, surveys of collection needs, number of printed books, titles of reference books, subscribed scientific journals, subscribed electronic journals, addition of printed book collections, number of electronic book collections, audio visual collections, number of brochures, leaflets, pamphlets, posters, subscribed databases, processing standards, enumeration, fumigation, and improvement of library materials.